Feminism at the Crossroads of Neoliberalism and Neoconservatism: Restructuring Women's Labor in the Context of Family Leave Reform in Finland - Ylöstalo Hanna (OXFORD UNIV PRESS, 2025)
This article analyzes the convergences of neoliberalism, neoconservatism, and feminism in the context of Nordic welfare state reform. Using Finland's ongoing family leave reform as an illustrative example, the article shows that neoliberalism, neoconservatism, and feminism find common ground in welfare state reform where workfare policies are intensified and the dismantling of the public provision is coupled with extended private sphere norms. The article unfolds neoliberal and neoconservative feminisms in the public policy context. It demonstrates that neoliberal and neoconservative feminisms contribute to restructuring women's labor by locating women as subjects critical to capitalist growth, competitive economies, national wealth, and balanced state budgets as providers of productive and reproductive labor. Moreover, they associate women's productive and reproductive labor with freedom and emancipation.